Integrating Hiem Aceh Ice Breakers in Islamic Religious Education: Impact on Student Engagement and Challenges - Sulhan Yus; Jarjani Usman; Zulfatmi Zulfatmi; Muji Mulia; Zubaidah Zubaidah (STAI Hubbulwathan Duri, 2025)
Hiem, a form of Acehnese oral tradition rich in riddles and local wisdom, is gradually being forgotten by the younger generation. Revitalizing this tradition through education offers opportunities to enhance students' cognitive abilities, linguistic skills, and cultural identity. This study explores the impact and challenges of integrating Acehnese hiem-based ice breakers into Islamic Religious Education (IRE) learning. This qualitative field study was conducted at SDN Trans Despot Leungah, Aceh Besar. Data were collected through interviews, classroom observations, documentation, and post-test assessments. The sample consisted of 30 respondents, including teachers and students selected through purposive sampling. Data were analyzed through thematic categorization following verification and triangulation. Findings indicate that the use of hiem-based ice breakers significantly increased student engagement, motivation, and enthusiasm during IRE lessons. Students demonstrated improved Acehnese language proficiency and better learning outcomes. Teachers and students positively perceived the integration of local cultural content into classroom activities. However, a notable challenge was language diversity; not all students were fluent in Acehnese, necessitating differentiated instructional strategies. The implementation of hiem-based ice breakers not only enhanced classroom interaction and student focus but also served as an effective tool to preserve and transmit Acehnese cultural heritage within formal education. While the impact is promising, broader application requires pedagogical adjustments to accommodate linguistic diversity and curriculum integration.